Impatiens occultans (Balsaminaceae), a newly recorded species from Xizang, China, and its phylogenetic position - Guo, Hui; Wei, Lai; Hao, Jia-Chen; Du, Yu-Fen; Zhang, Lin-Jing; Yu, Sheng-Xiang (Phytotaxa, 2016)
Impatiens occultans Hook. f. (Balsaminaceae) is newly recorded for China, from Gyirong County, Xizang Province. A morphological description and notes on its distribution and ecology are provided. A phylogenetic analysis yields a placement of the species that it is sister to I. tuberculata (sect. Racemosae) with which it agrees in having a navicular lower sepal without a spur and 4-colpate pollen grains, but differs in elliptic leaves, 1-flowered racemes, 4 lateral sepals and glabrous capsules.